An Analysis Of Generic Structure Of Descriptive Text Written By The Eighth Grade Students Of Junior High School Darunnajah Duri - Devi Linda Wanti, Sri (Jolly Journal of English Education, 2024)
This research aimed to analyze the generic structure of Descriptive text written by the Eighth grade students of Junior High School Darunnajah Duri. The data sources of this research were 30 students of Eighth grade students which were taken by Cluster random sampling. The writer use quantitative approach and descriptive design. In this research the data were taken by using written test. The findings show the percentage of the students in writing the right identification paragraph was 53% or 16 students and 73% or 22 students can write description paragraphs in descriptive text. While the students’ score in writing the generic structure of Descriptive text, it was conclude that from the results the writer obtains data analyze mean value of 58.33.